IMPROVING THE CAPACITY OF PREGNANT WOMEN WITH “PEKAN BUMI BERCERITA” IN KALISONGO VILLAGE, MALANG - Yudianti, Ika; Mardiana, Heppy; Kusuma, Ratih (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
The 2005-2025 National Long-Term Development Plan has placed the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) as indicators of health levels and the success of implementing health development. Therefore, there needs to be an innovative program to empower pregnant women with "PEKAN BUMI BERCERITA" namely Joint, Cheerful, Calm, and Safe Pregnant Women's Health Education. This activity aims to increase mothers' knowledge about fulfilling the nutrition of pregnant women so that mothers go through their pregnancies cheerfully and prepare for childbirth calmly and safely. Community service activities were carried out on May 2, 2024 at the PAUD Hall, Kuso Hamlet, Kalisongo Village, Dau District, Malang Regency, targeting pregnant women. Women's empowerment activities use the Partipatory Learning and Action method "PEKAN BUMI BERCERITA", such as health education and edugames. The results showed an increase in pregnant women reaching 60% regarding the fulfillment of nutrition for pregnant women and preparation for childbirth.